Use of bulldog vascular clamps and vessel loops to reduce intraoperative bleeding during cesarean hysterectomy for placenta percreta - Juhul Patel; Vinutha Arunachalam; Rachita Munjal (Apollo Medicine)
Placenta percreta is a potentially life-threatening condition that requires a multidisciplinary team approach for optimal management. Bulldog vascular clamps were used to reduce the severity of bleeding among two patients undergoing cesarean hysterectomy for placenta percreta. Permanent hypogastric artery ligation can cause serious intraoperative and postoperative complications, especially when performed by inexperienced surgeons. Placing a bulldog vascular clamp across the internal iliac artery can reduce intraoperative bleeding and prevent serious complications associated with permanent hypogastric artery ligation.